DETECTION OF BETA GLOBIN GENE MUTATION BY CELL-FREE FETAL DNA (CFF-DNA) USING PYROSEQUENCING (DEVELOPMENT OF PRENATAL DIAGNOSIS IN BETA THALASSEMIA) - Setia Rahayu, Nurul
Beta thalassemia is a hereditary blood disorder caused by mutations of the beta-globin gene. It causes a decrease or the absence of beta-globin chains to form hemoglobin A. There are three types of beta-globin gene mutations in Indonesia, namely IVS1nt5 (G>C), Cd26 (G> A), and IVS1nt1 (G> T). The preventive steps of Beta -Thalassemia is a prenatal diagnosis test on pregnant women. The purpose of this study was to optimize a non-invasive prenatal diagnosis by using Allele Quantification (AQ) Pyrosequencing. The group of this study was 14 parents of Thalassemia patients, 10 pregnant mothers from Thalassemia patients, and 16 DNA-mutated beta-thalassemia patients as a positive control. Isolation of cell-free fetal DNA (cffDNA) from blood plasma was carried out for the first step, followed by the maternal contamination tests with PCR Variable Number Tandem Repeat (VNTR) at the ApoB and D1S80 loci. The detection of gene mutations with AQ Pyrosequencing was done for the final step. The results showed that 7 samples from 10 cffDNA samples were passed the maternal contamination test, which was followed by the detection of the Thalassemia Beta mutation. The AQ pyrosequencing on positive controls revealed that the threshold value of the percentage for each mutant allele was A (32%), T (23%), and C (39%). The prediction of the type of mutation based on the threshold value was that all parents were carriers of the beta-Thalassemia with IVS1nt5 mutation. Six fetal samples were predicted to be IVS1nt5 carriers. In contrast, 1 sample was predicted to be normal. In conclusion, the AQ pyrosequencing can be used to detect the beta-globin gene mutation by cffDNA in prenatal beta-thalassemia. The minimum threshold value for mutant alleles was A: 32% (Cd26), T: 23% (IVS1nt1), and C: 39% (IVS1nt5).